Worst-case analysis of the perception and exponentiated update algorithms. - Bylander, Tom (Artificial intelligence.)
The absolute loss is the absolute difference between the desired and predicted outcome. This paper demonstrates worst-case upper bounds on the absolute loss for the Perception learning algorithm and the Exponentiated Update learning algorithm, which is related to the Weighted Majority algorithm. The bounds characterize the behavior of the algorithms over any sequence of trials, where each trial consists of an example and a desired outcome interval (any value in the interval is an acceptable outcome). The worst-case absolute loss of both algorithms is bounded by: the absolute loss of the best linear function in a comparison class, plus a constant dependent on the initial weight vector, plus a per-trial loss. The per-trial loss can be eliminated if the learning algorithm is allowed a tolerance from the desired outcome. For concept learning, the worst-case bounds lead to mistake bounds that are comparable to past results.